2017
DOI: 10.12788/jhm.2714
|View full text |Cite
|
Sign up to set email alerts
|

Automating Venous Thromboembolism Risk Calculation Using Electronic Health Record Data Upon Hospital Admission: The Automated Padua Prediction Score

Abstract: Automated calculation of VTE risk had similar ability to predict hospital-acquired VTE as manual calculation despite differences in how often specific scoring criteria were considered present by the 2 methods. Journal of Hospital Medicine 2017;12: 231- 237.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 20 publications
0
47
1
Order By: Relevance
“…Whereas a score of 4 or more on the APPS indicating a "high risk" patient was reliable, there were considerable false negatives in the "low risk" group. A previous study comparing APPS to manual calculation found observed mean scores to be slightly higher in the manual group, although the difference was not statistically 20 That study did not report proportion of each group that would have been identified as high or low risk for VTE occurrence, so we cannot compare directly to our findings. Our primary objective was to examine how accurately the automated algorithm predicted high-versus low risk stratification of patients, as this is how the PPS is used clinically.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Whereas a score of 4 or more on the APPS indicating a "high risk" patient was reliable, there were considerable false negatives in the "low risk" group. A previous study comparing APPS to manual calculation found observed mean scores to be slightly higher in the manual group, although the difference was not statistically 20 That study did not report proportion of each group that would have been identified as high or low risk for VTE occurrence, so we cannot compare directly to our findings. Our primary objective was to examine how accurately the automated algorithm predicted high-versus low risk stratification of patients, as this is how the PPS is used clinically.…”
Section: Discussioncontrasting
confidence: 57%
“…Similar to results by Elias et al, we found that the differences in the performance between manual and automated data extraction methods for the PPS were largest among the individual variables for acute conditions, such as active cancer, acute infection, as well as for previous VTE. 20 The automated definitions for these variables rely heavily on diagnostic coding in the EHR. Risk for undercoding diminishes the likelihood that automated algorithms will capture certain PPS conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal approach to VTE risk assessment is not known, 12,26 but guidelines either offer no specific guidance 7 or would require implementation of 3 different systems per hospital. 4,5 Several of these are point scoring systems, which may have lower clinician acceptance or require programming to improve real-world use 18,26,27 ; the Padua score was derived from a patient population that differs significantly from those in the United States. 12 Our study provides more practical experience with a "3-bucket" model, which has previously shown high interobserver reliability, good clinician acceptance, and meaningful reductions of VTE, including in American patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with new surgical techniques, pain management protocols, neuroaxial anesthesia methods, early mobilization, and individualized VTE prophylaxis gained popularity to provide both effective VTE prophylaxis and prevent major and minor bleeding complications. [4][5][6] Guidelines recommending mechanical and pharmacological methods for VTE prophylaxis are regularly renewed. These include the American College of Chest Physicians (ACCP), [7] the American Academy of Orthopedic Surgeons (AAOS), [8] and the National Institute for Health and Care Excellence.…”
mentioning
confidence: 99%